The role of foreign NGOs in the development of local economy of aceh after tsunami - Erwansyah, Teuku; Jusoh, Hamzah (2008)

(untitled)
The earthquake and tsunami in Aceh on December 26th, 2004 have caused massive destructions. The World Bank noticed that, besides causing the death of the people, the destruction costs USD 41,401 billion, which 78% of it is in economical and environmental sectors. The rest is the destruction of local socio-cultural sector. The objective of this research is to investigate the role of NGOs to develop the local people in Aceh both economically and environmentally. The primary data will be obtained by distributing questionnaires while the secondary data will be taken from various sources such as agencies which have involved in the development of the local area for three years after the tsunami. A direct observation will be done applying two stratified cluster samplings. The research will be focused on some districts and villages in Banda Aceh where the tsunami impacts destruct massively. The analysis unit is the victims of tsunami. The Cobb-Douglas model will be used as to determine the input which significantly influences the income of the villagers. The impact of the role of NGOs to the local environment will be analyzed descriptively. The result is expected to be able to contribute to the authorities and the people about increasing the role of NGOs to empower the local people after tsunami.